Analysis of Energy Management and Battery Sizing in an Off‐Grid Hybrid Solar Thermoelectric Generation System. Issue 3 (20th January 2022) - Malik, Muhammad Suleman; Azmatullah, Umer; Khan, Muhammad Omer; Abu Bakr, Muhammad; Ahmad, Mubasher
Abstract : Herein, the main aim is to analyze the idea of utilizing the thermal energy generated during the operation of a solar photovoltaic panel. The rise in temperature of the solar panels and the surrounding environment results in the reduction of the generated energy and ultimately the efficiency of solar panels. This thermal energy can be utilized to generate electrical energy by installing thermoelectric generators at the backside of the solar panel. The electrical energy generated through a thermoelectric generator depends on the temperature difference at its surface, which could be formed through any cooling mechanism such as natural air or cold water circulation. The electrical energy generated from the solar panels and thermoelectric generator can be integrated as a hybrid source, resulting in an enhancement of the overall efficiency of the system. On the other hand, designing a proper energy storage mechanism can enhance the efficiency and overall sustainability of the proposed idea. The results show that in doing so, not only does the solar panel temperature decrease resulting in the increase of its efficiency but utilizing the thermal losses by the hybrid solar thermoelectric generation system can enhance the energy generation up to 31.89% at a temperature difference of 34.4 °C. Abstract : The thermal energy losses due to rise in temperature in the photovoltaic panels can be utilized and converted into electrical energy using a thermoelectric generator. This hybrid photovoltaic thermoelectrical system along with a proper battery storage system results in enhancing the overall efficiency of the system.